Comparative Government - Blondel, Jean. author. aut Link
L, 270 p.
Keywords: This textbook provides a comprehensive and systematic analysis of the institutions and patterns of behaviour of the countries of the contemporary world. The various political systems are compared and contrasted both in general terms and according to their characteristic structures. today, the characteristics and the role of groups, and the effect of the communications media. It examines in depth the origins, bases, and structures of political parties, the type of party system and the overall role of parties in contemporary politics. It then goes on to examine the formal institutions, analyzing the role of constitutions, the extent of decentralization, the characteristics of legislatures and the structure and impact of executives and political leaders. A final section is devoted to the part played by bureaucracies, the military and the courts in political life and discusses the extent to which ordinary people participate directly in politics.